A Typology of Crowdwork Platforms. (February 2019) - Howcroft, Debra; Bergvall-Kåreborn, Birgitta
Despite growing interest in the gig economy among academics, policy makers and media commentators, the area is replete with different terminology, definitional constructs and contested claims about the ensuing transformation of work organisation. The aim of this positional piece is to provide a timely review and classification of crowdwork. A typology is developed to map the complexity of this emerging terrain, illuminating range and scope by critically synthesising empirical findings and issues from multidisciplinary literatures. Rather than side-tracking into debates as to what exactly constitutes crowdwork, the purpose of the typology is to highlight commonalities rather than distinctions, enabling connections across areas. The framework serves as a heuristic device for considering the broader implications for work and employment in terms of control and coordination, regulation and classification, and collective agency and representation.